Tunable Glue : Rubber Elasticity Control of Adhesion at Polymer/Metal Interface - Sureurg KHONGTONG; Gregory S FERGUSON (Walailak Journal of Science and Technology, 2011)
The adhesion at this interface could be switched on and off just by lowering and raising temperature. A treated surface of 1,4-polybutadiene provides strong adhesion to aluminum at room temperature due to the interaction between hydrophilic functional groups, introduced by surface oxidation, and Al2O3 -native oxide on aluminum surface. This interaction also acts as an enthalpic driving force to stretch chains at the interfacial region of an elastomer to entropically unfavorable condition. Increasing temperature, in turn, induces these stretched interfacial chains to recoil in order to increase entropy of the system, thereby functional groups are pulled away from the elastomer/aluminum interface leading to the weakening of adhesion.